Affective components of the study on entering to the university - Stasiejko, Halina; Universidad de Buenos Aires (Editorial Pontificia Universidad Javeriana, 2012)
We are presenting the advance of a research whose objective is to delimit and to characterize the conceptions and the emotions that, within the study, assumed by first-year students. It is considered they can favor and/or obstruct the organization of activities of study needed for the inclusion and stay in the new environment. The authors synthesize the general theoretical conceptual framework, the qualitative methodological strategy selected and the results reached after the analysis of the data on the basis of “Grounded Theory”, that reveal the importance of the work about conceptions and emotions to favor the stay in the university.